Dynamic Modelling of Domestic Prices with Time-varying Elasticities and Rational Expectations - Ingvild Svendsen (Statistics Norway, Research Department, 1995)
The paper analyses the price on domestic market for an aggregate commodity produced by Norwegian private mainland economy. The long-run solution is modelled assuming imperfect competition. The elasticities with respect to unit labour costs and competing prices vary with an indicator for competitive strength in domestic market. I consider two models for the dynamic part of the equation. Model A is a conditional ECM in current and lagged variables. Model B is derived from a multiperiod quadratic loss function which introduces rational expectations to the model. The backward-forward restrictions are not rejected. The estimated elasticities for both models are in line with the previous empirical results for the Norwegian economy. Model A is preferred to Model B, partly on the basis of informal encompassing results.
Keywords: C22; D43; D84; 330; Domestic prices; Imperfect competition; Time-varying elasticities; Multiperiod loss function; Rational expectations; Error correction models